Pendekatan, Metode, Teknik Pembelajaran Bahasa Dan Sastra - Putrayasa, Ida Bagus; I Nyoman Sudiana; Dewa Nyoman Suardana; Yanti Maliani; Mekson Fernandes Landu; Ni Nyoman Ayu Yuliastri; Sarwan Hamid (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2024)
Learning approaches, methods and techniques are concepts frequently used in educational contexts, and although they are often used together, they have important differences. a. A learning approach refers to a general view or philosophy that guides the learning process. b. Learning methods are a series of techniques or strategies used by educators to convey lesson material to students. c. Learning techniques are special tools or strategies used in the context of learning methods to improve students' understanding and acceptance of subject matter. then several approaches in learning Indonesian Language and Literature that can be applied include formal, empirical, structural, skills, rational, functional, integrated, integral, sociolinguistic, psychological, psycholinguistic, communicative approaches. Therefore, in learning Indonesian language and literature, there are several methods that can be applied, namely lecture methods, question and answer, discussion, group work, sociodrama, demonstrations, experiments, recitations, field trips. and there are several techniques in learning Indonesian language and literature, namely techniques in learning to listen, techniques in learning to read, techniques in learning to speak, techniques in learning to write.